ยุทธศาสตร์การพัฒนาครูเพื่อจัดการเรียนการสอน ตามแนวสะเต็มศึกษา ในสถานศึกษาขนาดกลางในภาคเหนือ - tangchuang, phasina - (Journal of Inclusive and Innovative Education, 2020)
The objectives of this study were to: 1. study the existing conditions of school teachers on STEM Education, 2. identify factors and conditions that effected to teachers on STEM Education, and 3. propose strategies for teachers competency development on STEM Education in medium sized schools. Mixed methods were employed in data gathering: in-depth interviewing, observation and verifying the strategies for teachers competency development on STEM Education. Key informants composed of 3 teachers who received Thailand STEM Education Teacher Awards from 3 schools located in northern provinces, 3 teachers who participated in competency development and 3 schools directors. Findings revealed that: 1. Every school is located in poor communities. They are teachers shortage in specific subjects. According to applying the STEM Education, teachers need cooperation among core mathematics, science and other teachers and innovative technology. 2. There are 2 most important key factors and conditions of success: teacher inspirations and school directors 3. Strategies for teachers competency development on STEM Education composed of: School directors must be leaders to stimulate teachers to deeply understand contexts and environments; They must build up better relationship with communities and invite local wisdoms to teamwork; They must turn crisis into opportunity by applying PLC among students and teachers; They must nurture internal and external collaborations, and finally school committees and everyone must listen to each other and find ways for sustainable development. It is also recommended that higher education instructors continue their teachings by applying STEM Education to nurture students’ creativity competences.